Metacognitive judgments-of-learning in adolescents with autism spectrum disorder. (May 2014) - Wojcik, Dominika Z; Waterman, Amanda H; Lestié, Claire; Moulin, Chris JA; Souchay, Celine
This study investigated metacognitive monitoring abilities in adolescents with autism spectrum disorder in two experiments using the judgment-of-learning paradigm. Participants were asked to predict their future recall of unrelated word pairs during the learning phase. Experiment 1 compared judgments-of-learning made immediately after learning and judgments-of-learning made after a delay. We found that both groups overestimated their memory performance but that overall there were no group differences in judgment-of-learning accuracy. Additionally, both groups displayed the standard delayed judgment-of-learning effect (yielding greater judgment accuracy in delayed compared to immediate judgments), suggesting that both groups were able to use appropriate information in making their judgments-of-learning. Experiment 2 assessed whether adolescents with autism spectrum disorder could regulate their study time according to their judgments-of-learning using a self-paced learning procedure. Results showed that both groups spent more time learning items given lower judgments-of-learning. Finally, Experiment 2 showed that judgments-of-learning and study time varied according to item difficulty in both groups. As a whole, these findings demonstrate that adolescents with autism spectrum disorder can accurately gauge their memory performance while learning new word associations and use these skills to control their study time at learning.